Characteristics of children on the autism spectrum who benefit the most from receiving intervention in inclusive versus specialised early childhood education settings. Issue 11 (15th September 2022) - Vivanti, Giacomo; Bent, Catherine; Capes, Kristy; Upson, Shannon; Hudry, Kristelle; Dissanayake, Cheryl; ,
Abstract: This study examined the factors associated with social‐communicative outcomes for children on the autism spectrum receiving early intervention in inclusive versus specialised early childhood education programmes. Fifty‐eight preschool‐aged children randomly assigned to receive the Group‐Early Start Denver Model (G‐ESDM) in either inclusive or specialised (i.e., autism‐specific) classrooms across one calendar year showed similar outcomes at group mean‐level across measures of communication and social behaviour. We examined factors moderating outcomes across settings. Novel moderation analyses revealed that higher baseline social interest and nonverbal cognitive skills were associated with increased social communication gains for children in the inclusive classrooms, but not for those in specialised settings. Children who spend more time paying attention to people and have higher cognitive skills might benefit from receiving early intervention in inclusive settings, whilst these factors might be less relevant for children educated in specialised settings. Lay Summary: This study examined the characteristics of children on the autism spectrum who benefit the most from receiving intervention in inclusive versus specialised early childhood education settings. Fifty‐eight preschool‐aged children were randomly assigned to receive an evidence‐supported intervention called the G‐ESDM in either inclusive or autism‐specific classrooms across one calendar year. Children who spent more time paying attention to people and had higher cognitive skills prior to receiving the intervention experienced more gains in inclusive settings. Conversely, these factors were unrelated to gains for children educated in specialised settings.